Intermolecular C—H...O, Cl...Cl and π–π interactions in the 2‐dichloromethyl derivative of vitamin K3. (15th December 2013) - Soave, Raffaella; Colombo, Pietro
<x xml:space="preserve">Abstract</x> The title 1, 4‐naphthoquinone, 2‐dichloromethyl‐3‐methyl‐1, 4‐dihydronaphthalene‐1, 4‐dione, C12H8Cl2O2, is a chlorinated derivative of vitamin K3, which is a synthetic compound also known as menadione. Molecules of (I) are planar and lie on a crystallographic mirror plane (Z′ = 0.5) in the space group Pnma. They are connected to each other by C—H...O hydrogen bonds, forming two‐dimensional layers parallel to the ac plane. In addition, Cl...Cl and π–π interactions link adjacent molecules in different layers, thus forming zigzag ribbons along the b axis, such that a three‐dimensional architecture is generated.